CFD simulations of transient fuel gases mixing, leakage and flammability in air - Pendyala, R. (Italian Association of Chemical Engineering - AIDIC, 2015)
Dispersion of fuel gases in air is very rapid during accidental release which can lead to minor asphyxiate to major explosion. Leakage of fuel gases poses an unseen threat due to odourless and colourless properties of gas components. A complete understanding of fuel gases mixing behaviours with air is very crucial to develop prevention or mitigation guidelines towards major accident. Various fuel gases transient dispersion behaviours are simulated by using computational fluid dynamics in simple geometries. Transient dispersion behaviour and flammability limits of major fuel gases, which include methane, hydrogen, ethane, propane, carbon monoxide and acetylene are simulated in 2D closed and open-top geometries. Formation of flammability region is predicted and compared for each component of fuel gas in the range of higher and lower flammability limits. It is found that dispersion rate of gases is considerably effected by the density difference between air and fuel gas. Spatial and temporal distributions of fuel gases are compared in closed and open-top geometries. Copyright Â© 2015, AIDIC Servizi S.r.l.,.